The Relationship Between Antenatal Care (ANC) Compliance And High-Risk Pregnancy During The COVID-19 Pandemic At Puskesmas Sukorame, Kediri - Ninne Gerdha Fardiyana; Susanti Pratamaningtyas; Erna Rahma Yani (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
High-risk pregnancy is a pregnancy with problems that cause complications for the mother and baby. Efforts to improve health services for pregnant women to detect high risks can carry out pregnancy checks according to established ANC service. Objective The research purposed to the relationship between ANC compliance and high-risk pregnancy during the covid-19 pandemic at Puskesmas Sukorame, Kediri. Quantitative research method with cross sectional approach. The population of all pregnant women TM III with a sample of 49 people who met the inclusion-exclusion criteria and determined by consecutive sampling. The research instrument used a questionnaire sheet and KSPR. The research data were analyzed using Chi Square statistical test. Results based of chi square test with ? = 0,1 and df = 2 was clarified that score of X2count (4,63) > X2table (4,605), which meant H0 was rejected and Ha was accepted. concluded there is a the relationship between ANC compliance and high-risk pregnancy during the covid-19 pandemic at Puskesmas Sukorame, Kediri.